Pluralisme Agama dalam Perspektif Islam - Gustia Tahir (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2011)
Religious pluralism is a contemporer discourse in religious community. It is discussed because there is a phenomenon that the religious conflict existing in society due to misunderstanding among the followers of religion. They respectively claimed the truth of their religion and thus have absolute right to enter the paradise, maeanwhile others have no opportunity and chance to teste the convenience of heaven. In this case, religious pluralism must be socialized to establish good harmony among the followers of religion